STUDI ALTRUISM: IDENTIFIKASI KEMUNGKINAN MENGINTRODUSIR ELEMEN ALTRUISM KE DALAM KONSTRUK MOTIVASI PADA ELABORATION LIKELIHOOD MODEL - Agus Abdurrahman (JURNAL STUDI MANAJEMEN ORGANISASI, 2014)
Studies on altruism in these marketing communications want to focus on changingconsumer attitudes and behavior as a result of a process of receiving information ormessage . The results of the research and writings that refer to concepts and theories ofaltruism has been published by Robert L.West (2006 ) , David K. Levine (1997 ) , Rajan PBagozzi Nataraajan and Richard (2000 ), which provides a starting point for a possiblereplay of the building concept and the theory of altruism in the context of marketingcommunications .Keywords : Marketing Communication, Consumer Behavior, Alturis